2021
DOI: 10.1186/s40634-020-00317-8
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of olecranon osteotomy only with 6′5 mm partially trheaded cancellous screw is a safe an effective method used in surgical management of distal humerus fractures

Abstract: Purpose The objective of this study is to demonstrate the safety and efficacy of the osteosynthesis with a 6.5 mm screw and washer of a Chevron shape olecranon osteotomy performed for the surgical approach of supraintercondylar fractures of the distal humerus, achieving union and complication rates better or similar to other published case series. Methods From 2009 to 2019, 26 patients underwent fixation of an olecranon osteotomy for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Five studies did not report an average follow-up time period but rather included a minimum follow-up time period for patients included in their study. 7 , 11 , 13 , 17 , 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies did not report an average follow-up time period but rather included a minimum follow-up time period for patients included in their study. 7 , 11 , 13 , 17 , 18…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 6 Newer techniques use a long, fully, or partially threaded cancellous screw (with or without a washer) spanning the osteotomy site. 7 Adding a stainless-steel wire in a figure-of-eight configuration (ie, a tension band) to the single cancellous screw has the benefit of additional compression at the osteotomy site. The use of plate and screw constructs is becoming more common, likely due to the low-profile nature of newer plates and the strength of locking screw constructs.…”
mentioning
confidence: 99%
“…In a case series of 26 patients who underwent IMSF of an olecranon osteotomy with a 6.5 mm screw and a washer, there was a 100% union rate at 1 year postoperatively, with 2 cases of delayed osteotomy consolidation. 6 Similarly, in a retrospective study that included 18 patients who underwent PF and 10 with IMSF, 1 patient in the PF group went on to nonunion with revision PF and subsequent union, while there was a 100% union rate in the IMSF group. 20 However, there is a lack of studies comparing patient-reported outcomes between PF and IMSF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies highlight the possible advantages of intramedullary screw fixation (IMSF) compared to plate or tension band constructs, notably the minimal tissue dissection and lack of hardware prominence, which might confer lower rates of wound healing complications and reoperation. 5 , 6 , 19 Intramedullary screw fixation is also an attractive option due to its relative simplicity compared to the more technical and time-consuming tension band or plate and screw constructs.…”
mentioning
confidence: 99%
“…Open reduction and internal fixation with plates with good articular reconstruction have demonstrated satisfactory clinical outcomes. Firm stabilization can be achieved through various methods of fixation of plates (9)(10)(11) . Among them, several mechanical studies have proved that double plate fixation provides more stable fixation than other methods (12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%